2010
DOI: 10.1002/ana.22138
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction between causative genes of DYT1 and DYT6 primary dystonia

Abstract: Primary dystonia is a movement disorder characterized by sustained muscle contractions and in which dystonia is the only or predominant clinical feature. TOR1A (DYT1) and the transcription factor THAP1 (DYT6) are the only genes identified thus far for primary dystonia. Using electromobility shift assays and chromatin immunoprecipitation (ChIP)-qPCR, we demonstrate a physical interaction between THAP1 and the TOR1A promoter that is abolished by pathophysiologic mutations. Our findings provide the first evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 24 publications
4
98
1
5
Order By: Relevance
“…Mutations in the THAP1 domain are thought to interrupt DNA binding, causing transcriptional dysregulation of THAP1 target genes [1]. A functional study in a THAP1 case with a frameshift mutation in the nuclear localizing signal region of THAP1 demonstrated an impaired nuclear import of mutant THAP1 in vitro [18]; THAP1 is reported to interact with the promoters of TOR1A , mutations of which cause DYT1 dystonia [19], TAF1 , implicated in DYT3 dystonia [20], and recently THAP1 has been reported to autoregulate its own expression [21]. Hence, studies of biochemical and cellular mechanisms may provide a link to abnormal motor control in DYT6 dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the THAP1 domain are thought to interrupt DNA binding, causing transcriptional dysregulation of THAP1 target genes [1]. A functional study in a THAP1 case with a frameshift mutation in the nuclear localizing signal region of THAP1 demonstrated an impaired nuclear import of mutant THAP1 in vitro [18]; THAP1 is reported to interact with the promoters of TOR1A , mutations of which cause DYT1 dystonia [19], TAF1 , implicated in DYT3 dystonia [20], and recently THAP1 has been reported to autoregulate its own expression [21]. Hence, studies of biochemical and cellular mechanisms may provide a link to abnormal motor control in DYT6 dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…Two reports demonstrate that THAP1 can bind the TOR1A promoter [100,101]; both find that DYT6 mutations impair this association. One of these studies [100] demonstrated that THAP1 could enhance the expression of a luciferase reporter linked to the TOR1A promoter, but no differences in torsinA mRNA or protein were observed in fibroblasts derived from DYT6 dystonia subjects.…”
Section: Thap1 (Dyt6)mentioning
confidence: 99%
“…Najnovije studije ukazuju na funkcionalnu povezanost THAP1 i TOR1A proteina, a time i na zajedničke molekularne osnove DYT6 i DYT1 distonije. In vitro studije su pokazale da se THAP1 vezuje za promotorski region TOR1A gena i reguliše njegovu ekspresiju (Kaiser et al, 2010;Gavarini et al, 2010). Pokazano je da wt THAP1 snižava ekspresiju TOR1A, dok mutirani THAP1 smanjuje ovu represiju nad TOR1A.…”
Section: Molekularno Genetička Osnova Dyt6unclassified
“…Međutim, u kultivisanim fibroblastima u kojima je THAP1 utišan pomoću RNK interferencije, ili u fibroblastima koji su nosili heterozigotnu THAP1 mutaciju, nije bilo značajnih promena nivoa ekspresije TOR1A (Kaiser et al, 2010). Slično, u limfoblastoidnim ćelijskim linijama bolesnika sa THAP1 mutacijama nije uočena promena u nivou TOR1A ekspresije (Gavarini et al, 2010). Moguće objašnjenje bi bilo da je THAP1-TOR1A interakcija patofiziološki relevantna samo u CNS-u ili čak samo u određenim podtipovima neurona.…”
Section: Molekularno Genetička Osnova Dyt6unclassified
See 1 more Smart Citation